Identification of long non-coding RNAs in two anthozoan species and their possible implications for coral bleaching - Chen Huang (Nature Portfolio, 2017)
Abstract Long non-coding RNAs (lncRNAs) have been shown to play regulatory roles in a diverse range of biological processes and are associated with the outcomes of various diseases. The majority of studies about lncRNAs focus on model organisms, with lessened investigation in non-model organisms to date. Herein, we have undertaken an investigation on lncRNA in two zoanthids (cnidarian): Protolpalythoa varibilis and Palythoa caribaeorum. A total of 11,206 and 13,240 lncRNAs were detected in P. variabilis and P. caribaeorum transcriptome, respectively. Comparison using NONCODE database indicated that the majority of these lncRNAs is taxonomically species-restricted with no identifiable orthologs. Even so, we found cases in which short regions of P. caribaeorum’s lncRNAs were similar to vertebrate species’ lncRNAs, and could be associated with lncRNA conserved regulatory functions. Consequently, some high-confidence lncRNA-mRNA interactions were predicted based on such conserved regions, therefore revealing possible involvement of lncRNAs in posttranscriptional processing and regulation in anthozoans. Moreover, investigation of differentially expressed lncRNAs, in healthy colonies and colonial individuals undergoing natural bleaching, indicated that some up-regulated lncRNAs in P. caribaeorum could posttranscriptionally regulate the mRNAs encoding proteins of Ras-mediated signal transduction pathway and components of innate immune-system, which could contribute to the molecular response of coral bleaching.